VALIDITY AND TEACHERS' RESPONSES TO THE IN ACTION LEARNING DESIGN GUIDEBOOK - Nurmala R; Usman Mulbar; Muhhammad Darwis; Murtafiah (Department of Mathematics Education Universitas Borneo Tarakan, 2025)
This study aims to develop and validate the In Action learning design guidebook for mathematics in junior high school, as well as test teachers' responses to the guidebook. The research method refers to the Plomp development model, which includes the Preliminary Research Phase, Prototyping Phase, and Assessment Phase. The instruments used were design book assessment sheets, expert response questionnaires, and teacher response questionnaires. The results of the study based on expert validation analysis at the Assessment Phase stage showed that all indicators in the guidebook were in the valid and very valid categories (average assessment ranged from 3.17 to 3.63), indicating the feasibility of the product for implementation. Teacher response trials showed